Da tradição e da ruptura em Los santos inocentes, de Miguel Delibes e Videiras de Cristal, de Luiz Antonio de Assis Brasil - Neres, Jorge Paulo de Oliveira (2009)
In this doctoral thesis, from reading the novels Los santos inocentes by Miguel Delibes and Videiras de cristal, Luiz Antonio de Assis Brasil, analyzes the development of each of the works, with emphasis on the technical procedures used by the authors discusses the role played by the characters, especially those seen as crazy, inappropriate, or disposed of innocent, common in literary text, as confirmed by historians, and the nature of the reports, from discussions about the presence or absence of matter extraction as historical discursive practice undelying the narratives. Similarly, perspective comparativista, part is assumed that the works join a common matrix, lacated in the ancient literature and sacred texts, an open, devoid of character to break with the past, permeate, however, ironic look at postmodernity. Is analyzed embodied in stylistic effects that make them, under the aesthetic point of view, art, literay art.